Analisis dan Implementasi Simulasi Monte Carlo untuk Prediksi Kebutuhan Gula berdasarkan Penjualan Bumbu Tabur XYZ - Oktavia, Chendrasari Wahyu; Natalia, Christine; suprata, Ferdian; Hindratmo, Astria (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2020)
The sales activity is a very important activity for the development and sustainability of a company. The sales are closely related to the requirement of raw material. By knowing the number of sales, a company can do estimate the amount of raw material required for production. However, so far still be found as a company that has its policies to determine a requirement of raw material as impact not use a raw material control method. The research purpose to determine the amount of sugar raw material requirement based on results number of sales seasoning XYZ with Monte Carlo simulation. Based on the analysis of data processing results. It was found that the number of sales from the simulation results in 2019 was quite high compared to the sales results during 2018 where the difference in sales simulation in 2019 and real data in 2018 was 62,334 kg. In terms of sugar supply, the total requirement for sugar in 2019 is also quite high, namely 186,756 kg, or the difference in requirement between simulation results and real data is 21,818 kg. This shows that the amount of requirement is directly proportional to sales.